Monetary Policy, Macroeconomic and Anomalies Interactions Post COVID in Developed and Eastern European Stock Markets - Mohd Yusoff, Zetty Zahureen; Bahrudin, Nur Zahidah; Suryani, Ani Wilujeng (Information Management and Business Review, 2023)
The purpose of this study is to examine the crucial factors amongst monetary policy and macroeconomic variables that spike the anomalies momentum on stock markets post-COVID-19 pandemic in selected Developed and Eastern European countries. This study uses panel data to measure the cross interactions of five stock exchanges based on unprecedented recovery in the European stock markets that yield astonishingly higher returns post-COVID-19, believed to be due to a perfect adoption of monetary policies (Exchange and Inflation Rates) and macroeconomic factor (Economic Growth) from January 2017 to December 2022. Findings suggest that the Exchange Rate and Economic Growth of the country are positively significant in influencing the Stock Market Performance in European stock markets. Additionally, the Inflation Rate surprisingly is negatively related to Stock Market Performance. Furthermore, local and foreign investors prefer to invest in a country that has a great adoption of monetary policies (stable Exchange Rate and lower Inflation Rates) as well as macroeconomic variables (resilient Economic Growth) for post COVID-19 economic landscape. For practical implications, the study suggests that the stock market performance, exchange rate, inflation rate, and economic growth of the country should be maintained and improved to attract fund inflows from local and foreign investments. To the best of the authors’ knowledge, this study is the first that examines the anomalous market momentum effect post-COVID-19 pandemic focusing on aspects, monetary policy, and macroeconomic variables. The momentum effect investing strategies that provide abnormal returns in different stock markets truly existed.